2016
DOI: 10.1097/mib.0000000000000744
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with the Development of Crohnʼs Disease in Inflammatory Bowel Disease-unclassified Patients Undergoing Ileal Pouch–anal Anastomosis

Abstract: Younger age at disease onset is the only clinical factor associated with the development of CD after IPAA for IBDU. Patients with IBDU undergoing IPAA with young age at disease onset should be counseled about the potentially higher risk of developing CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Another study about pediatric-onset IBDU showed that patients with a family history of CD and treatments including surgery, steroids, cyclosporine, anti-TNF and nutritional support were more likely to be diagnosed with CD [ 32 ]. Additionally, Sharon Z. Koh et al discovered that the only clinical factor related to CD reclassification after IPAA for IBDU was younger age at disease onset [ 33 ]. As our IBDU patients commonly present for medical evaluation during the intermediate phase, individualized treatment can be implemented based on the identified factors mentioned above before reaching the final differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study about pediatric-onset IBDU showed that patients with a family history of CD and treatments including surgery, steroids, cyclosporine, anti-TNF and nutritional support were more likely to be diagnosed with CD [ 32 ]. Additionally, Sharon Z. Koh et al discovered that the only clinical factor related to CD reclassification after IPAA for IBDU was younger age at disease onset [ 33 ]. As our IBDU patients commonly present for medical evaluation during the intermediate phase, individualized treatment can be implemented based on the identified factors mentioned above before reaching the final differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the only factor associated with the development of de novo CD after IPAA in IBD‐U is younger age at disease onset. [19] Biologically, patients diagnosed at a younger age or in childhood may be exposed or respond differently to various microbial antigens as compared to adults, resulting in a more persistent immune reactivity. [20] Alternatively, this may simply represent a function of time, as the longer duration of microbial antigen exposure may increase eventual rate of conversion to another form of mucosal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Restorative proctocolectomy with IPAA is the standard surgical treatment for UC (Buskens 2014;Koh 2016), and approximately 15% of patients with UC undergo a colectomy within 10 years of diagnosis (Frolkis 2013). IPAA involves the construction of an internal pouch utilizing a distal portion of the remaining small intestine to create a reservoir for stool (McGuire 2007).…”
Section: Description Of the Interventionmentioning
confidence: 99%